INTEREST IN IMPLEMENTATION OF FINANCIAL INFORMATION SYSTEMS FOR SME’S - Iswahyudi, M.; Hurotul'Aini, Winda; Narulita, Sari (RADJA PUBLIKA, 2023)
This study aims to determine the interest of SMEs in using accounting information systems. The interest of MSME actors is measured using the effectiveness of the implementation of financial information systems. In addition, the attitude variable is used to bridge the relationship between the perceptions of MSME actors related to ease of use, usability, risk and trust in the effectiveness of the information system used. The survey method using a questionnaire was used in this study. the results of the study show that attitude determines the effectiveness of the implementation of financial information systems by MSME actors. This study also found that in order to bring out a positive attitude from users of financial information systems, it is necessary to pay attention to the usefulness of financial information systems that are created and trusted by MSME actors.